MANAJEMEN INFAQ SECARA SEKTORAL DI BAITUL MAAL HIDAYATULLAH (BMH) CABANG MALANG - Nurwakhidah, Ana (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
This study aims to describe the management of sectoral basis at BMH infaq Malang, analyzing constraints in the management of sectoral basis at BMH Infaq Malang, and analyze the steps in Malang BMH anticipating the obstacles facing it. This research was qualitative research with the descriptive approach. In the study described the management of sectoral Basis Infaq Baitul Maal Hidayatullah (BMH) Malang. From the analysis results can be concluded that the implementation of the management of sectoral basis infaq Baitul Maal Hidayatullah (BMH) Malang is by applying the characteristics of Islamic managements, namely: management based on the morals of the sublime, management Open, democratic management, management, and management tolong-menolong based upon peace, and perform management functions, namely, the Act of planning, organizing, and monitoring. Management functions are performed so well that gathering together the funds, and the channelling of funds in sectoral infaq, runs well and right on target, but nevertheless the function of surveillance need to be improved both in terms of its compilation or distribution to the various sectors.